A spatial econometric analysis of cultural dimensions, technology knowledge and economic growth - Barboza, Gustavo A.; Pede, Valerien O. (Wiley, 2012)
Using data from 65 countries over the period 1980–2003, this paper investigates the role that cultural dimensions play in the process of technological change, innovation and adoption and consequently on the steady state level of output per worker and its growth, using spatial econometrics techniques to account for spatial dependence between countries. Initial findings indicate that differences across cultural dimensions act as a leveling effect but not as long run growth determinants. In addition, when controlling for physical and human capital accumulation, culture plays a much smaller role in explaining differences in income per capita than initially thought, with little effect on output per worker growth along the transitional dynamics path. Spatial econometric considerations are relevant in explaining differences across rates of growth of per worker output, but not in terms of steady‐state levels of income.